Social dimensions of procurement auctions for environmental service contracts: Evaluating trade-offs between cost-effectiveness and participation by the poor in rural Tanzania - Jindal R; Kerr JM; Ferraro, P.J.; Swallow, B.M. (Elsevier, 2013)
Determining the level of payment and selecting participants are important but frequently neglected issues that affect social, economic and environmental performance of payment for environmental services (PES) programs. We use a pilot auction to address these issues in the context of a PES program in Tanzania's Uluguru Mountains. Two-hundred fifty-one local farmers submitted sealed bids in the auction. The results reveal the supply of PES contracts at different prices. Simulations using the auction results and household data show large tradeoffs between achieving cost effectiveness and maximizing participation by poor households. A monitoring survey 21 months after the auction found that most auction winners trees had survived, with performance uncorrelated to the farmer's poverty status or bid level. Although aspects of our auction design limit the strength of some of the conclusions we draw from the data, our study shows how pilot auctions can assist decision makers in estimating payment levels for PES contracts. Auction participants stated that the auction provided transparency in contract allocation and that winners felt peer pressure to comply with contracts, which suggest areas for future research regarding the potential advantages of using auctions to allocate PES contracts in developing countries.